PERAN KOPERASI JASA MENENUN MANDIRI DALAM MENINGKATKAN STATUS SOSIAL EKONOMI PENGRAJIN TENUN IKAT - Rika, Liliana; Khosmas, F. Y.; Witarsa, Witarsa (Universitas Tanjungpura, 2023)
This study aims to analyze the role of the Koperasi Jasa Menenun Mandiri (JMM) in assisting woven craftsmen in Sintang Dalam Regency improve economic status. The research approach used in this study is a qualitative research with the type of case study research. In decidingthe research sample used the snowball sampling technique, while the sample in take as informants are managers and woven craftsmen who are members JMM cooperative. Data collection techniques used were observation, interviews, and documentation, using observation guides and interviews as tools helpwith data collection. The data obtained were analyzed by reducing, presentation, and verification data. The research results show that in running its role, the cooperative creates jobs, a tourism center for woven textiles,increase members' income, increase sales of woven cloth, give training, holding RAT (Annual Member Meeting), and providing services savings and loans that benefit members. The role of the JMM Cooperative provides the impact is in the form of increasing member income so that the quality of life of members as well increased, in addition to an increase in the number of sales of woven fabrics and training given the JMM Cooperative also strengthens the member's economy, and in the management of the JMM Cooperative also plays a role based on kinship and democracy which can be seen from RAT activities and savings and loan services he gave